Domestic or Foreign Banks? Who Wields more Market Power? - Abel, Sanderson; Khobai, Hlalefang; Le Roux, Pierre (International Journal of Economics and Financial Issues, 2017)
The study distinguishes the market power between domestic and foreign banks in Zimbabwe using the Lerner Index. The study established that the banking sector is operating under monopolistic competition conditions. The result shows banks price their products above the marginal cost of production. Domestic banks have more market power as compared to foreign firms. The foreign banks serves the high end consumers whose risky profile is low while the other end of the market is served by the domestic banks who are very risky. This then translates to higher prices for the clients served by the domestic banks. Bank regulators should promote competition to improve the efficiency of domestic banks to reduce their market power. Keywords: Market Power, Lerner Index, Marginal Cost JEL Classifications: D4, G21, L1